Thermal hydrolysis prior to hydrothermal carbonization resulted in high quality sludge hydrochar with low nitrogen and sulfur content - Liu, Xiaoguang (Waste management (New York, N.Y.), 2024)
Copyright © 2024 Elsevier Ltd. All rights reserved.